CGIAR Climate Impact Platform Coordinated CGIAR Participation at COP29 in Baku, Azerbaijan and Bonn Climate Conference Bringing Greater Coherence and Impact - Edward-Uwadiale, Regina (CGIAR Climate Change Impact Platform, 2024)
The CGIAR Climate Impact Platform has played a pivotal role in enhancing the coherence and impact of CGIAR's contributions to global climate processes, particularly at COP29 and the Bonn Climate Conference. By strategically coordinating workstreams, the Platform has ensured seamless representation and active engagement across critical negotiation tracks, aligning CGIAR's work with broader climate goals. Key deliverables, such as daily briefs, issue briefs, and high-profile events, have not only informed but also influenced global climate discussions. This paper delves into the Platform's meticulous planning and execution of these initiatives, spotlighting its ability to convene stakeholders, streamline communications, and drive impactful advocacy. Through these efforts, the Platform has reinforced CGIAR’s position as a leader in advancing agricultural innovation and climate resilience within the global climate agenda.